Les alcaldes de barrio de Madrid (1834-1840) : une police urbaine de voisinage « entre ancien et nouveau régime » - Mathieu Aguilera (Nuevo mundo - Mundos Nuevos, 2017)
After the Absolutist Restoration, the Liberals gradually undertook to dismantle the Old Régime’s institutions, in particular the Sala de Alcaldes de Casa y Corte. However, this process did not immediately modify the police powers of the Alcaldes de barrio in the capital city. These local notables, invested by the municipal corporation to take on numerous administrative tasks (social regulation and supervision), offer a good opportunity to observe the changes of the jurisdictional system at the time of the first reforms of the Justice administration in 1835. The Municipality and governments have been able to rely on these local agents, who were closer to the inhabitants, in order to govern the city.